Rationale and design of the Chinese Atrial Fibrillation Registry Study. Issue 1 (December 2016) - Du, Xin; Ma, Changsheng; Wu, Jiahui; Li, Songnan; Ning, Man; Tang, Ribo; Guo, Xueyuan; Long, Deyong; Yu, Ronghui; Sang, Caihua; Jiang, Chenxi; Zhang, Ting; et al.
Abstract Background Robust data on the contemporary management of atrial fibrillation (AF) patients in China are limited. Importantly current practice in AF management has changing dramatically in recent years. Data from a large registry study will enable us to evaluate the uptake and outcomes with different therapies in a large Chinese AF population. Methods/Design The Chinese Atrial Fibrillation Registry study (CAFR) aims to enroll 20, 000 consecutive atrial fibrillation (AF) patients from 32 tertiary and non-tertiary hospitals in Beijing, China, and follow up these patients every 6 months until 2020. Key data collected includes basic sociodemographic information, symptoms and signs, medical history, results of physical examination and laboratory test, details of treatments and personal insurance status. For patients who consent, 5 ml of blood sample will be stored at −80 °C for future analyses of biomarkers. At each 6 month follow up visit, data relating to clinical outcomes will be collected. Data from a randomly selected 10 % of patients will be internally validated with their raw source data. Ischemic stroke events will be adjudicated by an independent endpoint committee. Discussion CAFR will be one of the largest registries of Asian AF patients (and the largest in Chinese AF patients), as well as providing the longest follow up. This study would provide a valuable opportunity for 'real world' clinical epidemiology with insights into the uptake (and outcomes) of contemporary AF management. Trial registration Chinese Clinical Trial RegistryChiCTR-OCH-13003729 . Registered 22 October 2013.